Factors influencing Vietnam's rice export to Europe - Mai, Nguyen Thi; Phuong, Tran Mai; Nhi, Tran Ngoc Uyen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
Vietnam is known as one of the biggest rice exporters in the world but its export value is not high and increases slowly. Rice importing partners of Vietnam are many world's biggest trading partners, such as America, Japan, China, Europe,…Especially, Europe is a great potential import market but Vietnam has not been able to exploit it effectively. Therefore, this paper examines the factors affecting the rice export activities of Vietnam into the European market. The series panel data of bilateral trade from 2000 to 2019 and the gravity model are used to estimate the export activities of rice. The results have revealed that the gross domestic product of Vietnam, the exchange rate of European countries (in VND/USD), institute quality of Vietnam positively affect the flow of rice trade; while per capita income of European countries, exchange rate of Vietnam (in USD/VND) and the geographical distance between Vietnam and importers impact negatively.